Cohesión familiar y el locus de control en los estudiantes de la Escuela de Educación Básica Adonai - Manobanda Quinatoa, Ángela del Pilar (2019)
Scholars have come to consider the family as an indisputable active agent of social development, as an element in which the characteristics of an individual are created and strengthened, where social crises are solved or accentuated and where the generality of people find affection and especially security within a social bond. Therefore, the statement of the problem of this research is the importance of family cohesion in the formation of the locus of control of students in recent years of basic education, allowing to know the problem about the family climate and locus of control that have adolescents, which will be a starting point for studies in other institutions, and with variables related to this problem. At a practical level, it will allow preventive or psychological intervention programs aimed at improving the family environment of the students, since the institution lacks specific workshops where it includes or of importance of the family climate that can be generated when difficulties arise that the children could Interpret as difficult challenges to overcome. This study will help as knowledge for the educational community about the family climate and locus of control of students who present academic or behavioral difficulties, to promote preventive measures such as raising awareness of families to understand the difficulties of their children and provide of information to face these difficulties.